Flat Stanley - Brown, Jeff; Greenhut, Josh.; Pamintuan, Macky (New York : Scholastic Inc, 2010)
"Based on the original Flat Stanley by Jeff Brown"--Verso t.p.
A picture book version of the story in which a bulletin board falls on Stanley while he is sleeping, and he finds that being flat has its advantages.
Keywords: Humorous stories